2019
DOI: 10.31128/ajgp-01-19-4831
|View full text |Cite
|
Sign up to set email alerts
|

Androgen deficiency in older men

Abstract: BackgroundOlder men, especially those who are overweight or obese and have comorbidities, not uncommonly present with non-specific androgen deficiencylike symptoms, such as low energy and sexual dysfunction, and modestly lowered serum testosterone relative to reference ranges based on healthy young men. ObjectiveThe aim of this paper is to describe the clinical approach to men who present with non-specific androgen deficiencylike symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…decreased HPG axis function) and/or pathological (e.g. medications, chronic diseases and obesity) factors can cause testosterone deficiency in men (Grossmann, 2019). Nutrition plays an important role in reducing depression, and some studies have shown that saffron can play an effective role in reducing depression.…”
Section: Introductionmentioning
confidence: 99%
“…decreased HPG axis function) and/or pathological (e.g. medications, chronic diseases and obesity) factors can cause testosterone deficiency in men (Grossmann, 2019). Nutrition plays an important role in reducing depression, and some studies have shown that saffron can play an effective role in reducing depression.…”
Section: Introductionmentioning
confidence: 99%